The Effect of Using Rock Type Classification Comparator Board Media In Contextual Learning on Geography Learning Outcomes Of Class X at SMAN 22 Surabaya - Nurjannah, Nurjannah; Prasetyo, Ketut (Journal Research of Social Science, Economics, and Management, 2024)
This study investigates the impact of using rock type classification comparator board media in contextual learning on the geography learning outcomes of grade X students at SMAN 22 Surabaya. The research employed a quantitative descriptive approach with a quasi-experimental design, involving pre-tests and post-tests for experimental and control groups. Data were collected through observations, questionnaires, and test instruments. The validity and reliability of the research instruments were confirmed through Cronbach’s Alpha values exceeding 0.6. Results indicate that the use of comparator board media significantly enhances student learning outcomes in terms of cognitive, affective, and psychomotor aspects. The Mann-Whitney Test revealed a significant difference between pre-test and post-test scores (p < 0.05), while the Spearman Rank Correlation showed varied results, with positive correlations in the affective aspect (0.611) and negative correlations in cognitive (-0.146) and psychomotor (-0.087) aspects. Despite the high cost of the media being a limitation, the tool’s functionality and its ability to foster collaborative learning make it effective in improving student engagement and understanding of lithosphere materials. This study highlights the importance of innovative teaching tools in enhancing learning outcomes.